Extrato de própolis de abelhas africanizadas microencapsulado em soro de leite como agente antioxidante em manteiga - Lima, Lidiana Souza Correia (2021)
This study aims to produce and characterize powder of propolis extract encapsulated in whey via spray dryer process and evaluate the use of the material obtained as a new natural antioxidant in butter. The drying optimization of the propolis extract by factorial design showed an optimal inlet air temperature of 172°C and an optimal feed flow of 5 mL.min-1. The microcapsules obtained showed moisture, hygroscopicity and solubility that ensured the good stability of the powder produced. The morphology observed indicates the formation of smooth and spherical microcapsules of different sizes and without cracks. The high efficiency of microencapsulation (83.7%) was confirmed from the antioxidant capacity values at DPPH (1220.6 μmol Trolox·g -1 ), ABTS (1050.6 μmol Trolox·g -1 ) and FRAP (5712.5 μmol Trolox g -1 ) and the presence of 36 bioactive compounds in the final composition of the powder. The kinetic study of the oxidation of butter added with 100 ppm of microencapsulated propolis powder in whey compared to the sample without antioxidant showed a reduction of 68.9% in the formation rate of primary oxidation products and 34.3% of secondary products after 42 days of storage at 50°C. In the presence of 100 ppm of BHT these reductions were 61.1% and 29.1%, respectively. Oxidative stability by the Rancimat method showed an induction period of 1 h longer for the whey encapsulated propolis powder sample (100 ppm) compared to BHT (100 ppm) and more than 5 h compared to the control sample (without antioxidant). In the sensory analysis, significant differences of 30% were observed between the control butter and the one added with 100 ppm of propolis powder. In general, the results obtained confirmed the feasibility of obtaining a natural antioxidant based on propolis extract encapsulated in whey, which can inhibit butter oxidation during its consumption time without noticeable sensory changes.